PT BUKIT ASAM'S STRATEGY IN INCREASING COMPETITIVENESS IN CHINA - Sukmanda, Selvi; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
International trade is an essential aspect of every country's economy. Economic benefits and domestic growth are achieved through the opening of trade with other nations. These impacts arise directly from changes in resource allocation and efficiency and indirectly through higher levels of investment. The Fourth Industrial Revolution has also fundamentally transformed the way people live, work, and create value worldwide. New technologies and applications connect individuals, organizations, and machines at an unprecedented scale and speed. This qualitative research employs data collection techniques sourced from books, journals, theses, official documents, reports, and websites relevant to the study. The research also adopts a mercantilist perspective with an analysis at the nation-state level, incorporating the concepts of national interest and competitive strategy. The findings of this study indicate that PT Bukit Asam’s strategy successfully enhanced operational performance by producing competitive outputs in 2023. This success resulted from efficient production methods and strong production performance supported by mining contractor services. Keywords: China, Coal, PT Bukit Asam, Global Market